2016
DOI: 10.1111/ctr.12824
|View full text |Cite
|
Sign up to set email alerts
|

Does asymptomatic recurrent diffuse capillary C4d complement deposition impair cardiac allograft function?

Abstract: Recurrent asymptomatic diffuse capillary C4d immunostaining may play a role in the early development of cardiac allograft adverse remodeling and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The ischemic time observed in this study (mean of 120 minutes) is similar to other transplant centers. Comparing to ischemic time reported by Frea et al, only 2 (3%) of our patients presented higher than 160‐minute ischemic time. The shorter ischemic time observed in our study probably contributed to the decrease in the ischemic injury inflammation.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The ischemic time observed in this study (mean of 120 minutes) is similar to other transplant centers. Comparing to ischemic time reported by Frea et al, only 2 (3%) of our patients presented higher than 160‐minute ischemic time. The shorter ischemic time observed in our study probably contributed to the decrease in the ischemic injury inflammation.…”
Section: Discussioncontrasting
confidence: 82%
“…The C4d capillary positivity has been routinely applied as a humoral injury marker, and the recurrent asymptomatic diffuse C4d immunostaining has a role in the early development of cardiac allograft's adverse remodeling and dysfunction . In this study, we investigated whether early intragraft C4d positivity could also influence the cardiovascular mortality in relation to long‐term transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, graft function was normal in 43% of C4d-positive patients. In the context of asymptomatic patients, Frea et al [7] reported that recurrent C4d EMBs were associated to adverse remodeling of left ventricle, and Wu et al [6] showed that asymptomatic patients with C4d EMBs were more likely to develop cardiac allograft vasculopathy (CAV). Interestingly, the relationship between immediately adverse outcomes, CAV and pAMR has been reported, in particular, when pAMR is detected later than the first year after transplant [9].…”
Section: Prognostic Features Of Pathological Features Of Antibody-med...mentioning
confidence: 99%
“…Kennel et al in 2018 identified 15 differentially expressed proteins during rejection using liquid chromatography–tandem mass spectrometry analysis of serum exosomes ( 52 ). Vesicles C4d + are the most common studied and are linked with humoral rejection ( 53 ), indeed Hu et al in 2020, after the purification of donors' heart exosomes with anti-donor HLA I antibody beads, identified C4d protein expression as marker for acute rejection ( 54 ).…”
Section: Introductionmentioning
confidence: 99%